Urethane prepolymer, adhesive, laminate, and synthetic artificial leather
By adjusting the viscosity and thermal softening temperature of the urethane prepolymer, the problem of the loss of adhesiveness of the moisture-curing adhesive and the low degree of processing freedom of the hot melt adhesive is solved, and a high degree of processing freedom of the adhesive that can be heat-pressed after moisture-curing is achieved.
Patent Information
- Application Number
- CN202411859256.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-05
- Filing Date
- 2020-08-24
- Publication Date
- 2025-02-28
AI Technical Summary
The existing moisture-curing adhesive loses adhesion after curing, while the hot melt adhesive has low processing freedom, making it difficult to meet the needs of high viscosity and high processing freedom.
By adjusting the viscosity and thermal softening temperature of the urethane prepolymer, it can be heat-pressed after moisture curing, achieving high processing freedom. Specific measures include adjusting the viscosity to 30-600 dPa·s at 100°C, blocking the isocyanate group with a blocking agent, and controlling the thermal softening temperature after moisture curing to 75-155°C.
The urethane prepolymer with high processing freedom after moisture curing is achieved, which not only has excellent physical properties but also improves the flexibility of the adhesive.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
This application is a divisional application of the invention patent application with application number 202080062087.9, application date August 24, 2020, and invention name "Urethane prepolymer, adhesive, laminate and synthetic leather". Technical Field
[0001] The present invention relates to a urethane prepolymer, an adhesive and synthetic artificial leather. Background Art
[0002] Moisture-curing adhesives are polyurethanes with isocyanate groups at the ends, which react with moisture (humidity) in the air to undergo a cross-linking reaction, thereby functioning as an adhesive. Usually, polyurethane-based adhesives use a two-component curing system, in which a multifunctional isocyanate is mixed with a polyurethane having a hydroxyl group at the end for cross-linking. In contrast, the above-mentioned moisture-curing adhesives have the advantage of being able to be applied without the trouble of mixing. However, the softening temperature after cross-linking is generally as high as 170 to 200°C due to the increase in molecular weight caused by cross-linking, so although the durable physical properties are sufficient, it does not have adhesiveness after curing. Therefore, it is necessary to continuously carry out the process from coating on one substrate to bonding on the other substrate.
[0003] On the other hand, hot melt adhesives are adhesives that bond substrates to each other by melting a solid adhesive by heating (for example, see Patent Documents 1 and 2). They have the advantage of being easy to use because they melt at around 100°C, but have the disadvantage of low durability (heat resistance, bending resistance, cold resistance, hydrolysis resistance, etc.) due to the composition and molecular weight. In addition, a dedicated melter must be used in some cases, and film coating or gravure coating (spot bonding, etc.) is difficult, resulting in low processing freedom.
[0004] In addition, as adhesives used for decoration of clothing, bags, and shoes, adhesives whose composition and molecular weight are adjusted to meet the above-mentioned durability properties are used. However, due to high viscosity and significant reduction in processing adaptability, hot melt resins dissolved in organic solvents are used, but solvent-free adhesives are recommended due to environmental regulations in recent years.
[0005] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2000-336142, Patent document 2: Japanese Patent Application Publication No. 2005-126595. Summary of the invention
[0006] Problems to be solved by the invention As described above, moisture-curing adhesives do not exhibit adhesiveness after curing, and hot-melt adhesives have low processing freedom. Therefore, if a moisture-curing adhesive can be heat-pressed like a hot-melt adhesive after curing, it is very meaningful to obtain excellent physical properties and improve processing freedom, but such an adhesive is still unknown in practical use.
[0007] Therefore, an object of the present invention is to provide a urethane prepolymer which can be thermocompression bonded after moisture curing and has a viscosity range with a high degree of processing freedom.
[0008] Means of solving problems The inventors of the present invention have conducted intensive research to solve the above-mentioned problems and have found that if the viscosity at 100° C. is within a predetermined range and the thermal softening temperature after moisture curing is within a predetermined range, a urethane prepolymer can be heat-melted after moisture curing to obtain a urethane prepolymer with high processing freedom, thereby arriving at the present invention. That is, the present invention is as follows.
[0009] [1] A urethane prepolymer having an isocyanate group, having a viscosity of 30 to 600 dPa·s at 100° C., and a thermal softening temperature of 75 to 155° C. after moisture curing.
[0010] [2] The urethane prepolymer according to [1], wherein 10 to 55% of the isocyanate groups relative to the total molar number are blocked with a blocking agent.
[0011] [3] The urethane prepolymer according to [1] or [2], which is a reaction product of a polyisocyanate and a polyol, wherein the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate to the hydroxyl group of the polyol is 1.2 to 2.5.
[0012] [4] An adhesive comprising the urethane prepolymer according to any one of [1] to [3].
[0013] [5] A laminate comprising a moisture-cured layer of a coating film containing the adhesive according to [4] on a base film.
[0014] [6] A synthetic artificial leather comprising a thermally pressed product of a base fabric on the moisture-cured product layer of the laminate according to [5].
[0015] Effects of the Invention According to the present invention, a urethane prepolymer can be provided which can be thermocompression bonded after moisture curing and has a viscosity within a range with a high degree of processing freedom. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] [ Figure 1]A schematic illustration showing the morphology of the sample used in the evaluation of the embodiment.
[0017] [ Figure 2 ] Description of the form of the Geer oven used in the evaluation of the examples. DETAILED DESCRIPTION
[0018] Hereinafter, an embodiment of the present invention (this embodiment) will be described in detail, but the present invention is not limited to this embodiment.
[0019] [1. Urethane prepolymer] The urethane prepolymer according to the present embodiment has an isocyanate group, has a viscosity at 100° C. of 30 to 600 dPa·s, and has a thermal softening temperature after moisture curing of 75 to 155° C.
[0020] If the viscosity at 100°C is less than 30 dPa, the penetration into the base fabric becomes significant, making processing difficult, and the hand feel after moisture curing becomes hard. If it exceeds 600 dPa, it becomes viscous and processing becomes difficult. The viscosity is preferably 50 to 250 dPa, more preferably 70 to 200 dPa.
[0021] In addition, if the heat softening temperature after moisture curing is lower than 75°C, it is easy to penetrate into the base fabric when it is made into synthetic leather, and the hand feel becomes hard, etc., and it is difficult to obtain good physical properties. If it exceeds 155°C, subsequent processing becomes difficult and the degree of processing freedom is reduced. The heat softening temperature is preferably 78 to 152°C, and more preferably 80 to 150°C.
[0022] The above-mentioned viscosity and thermal softening temperature can be measured by the method described in Examples.
[0023] In order to make the viscosity at 100°C before moisture curing within the above range, the type of polyol and the NCO / OH ratio are adjusted, and in order to make the thermal softening temperature after moisture curing within the above range, it is preferred to use a blocking agent to block a part of the isocyanate groups in the urethane prepolymer. By blocking, the amount of isocyanate groups can be controlled, the softening point can be lowered, and the physical properties can be maintained. By blocking with a blocking agent, unlike, for example, blocked isocyanates whose blocking agents are thermally dissociated, it is easy to control the thermal softening temperature after moisture curing to 75 to 155°C because the blocking agent is difficult to thermally dissociate. As a result, a urethane prepolymer that can be moisture cured and heat-pressed and has a high degree of processing freedom can be obtained.
[0024] Examples of the blocking agent include lactams such as ε-caprolactam, δ-valerolactam, and γ-butyrolactam, aliphatic amines (dimethylamine, diisopropylamine, di-n-propylamine, diisobutylamine, etc.), alicyclic amines (methylhexylamine, dicyclohexylamine, etc.), aromatic amines (aniline, diphenylamine, etc.), aliphatic alcohols such as methanol, ethanol, 2-propanol, n-butanol, cetyl alcohol, isostearyl alcohol, oleyl alcohol, behenyl alcohol, lauryl alcohol, lanolin alcohol, hydrogenated lanolin alcohol, and 1-hexadecyl alcohol, phenol, cresol, ethylbenzene, Phenols such as phenol, n-propylphenol, isopropylphenol, n-butylphenol, octylphenol, nonylphenol, xylenol, diisopropylphenol, di-tert-butylphenol, imidazoles such as imidazole and 2-methylimidazole, pyrazoles such as pyrazole, 3-methylpyrazole, 3,5-dimethylpyrazole, aziridine, active methylene groups such as dimethyl malonate, diethyl malonate, propylene glycol diisopropyl ester, acetylacetone, methyl acetoacetate, ethyl acetoacetate, oximes such as acetone oxime, methyl ethyl ketone oxime, cyclohexanone oxime, etc.
[0025] Among them, from the viewpoint of reactivity and control of synthesis, aliphatic alcohols are preferred, and aliphatic alcohols having 10 or more carbon atoms are more preferred.
[0026] From the viewpoint of making the thermal softening temperature after moisture curing within the desired range, it is preferred that 5 to 60% of the isocyanate groups are blocked by the blocking agent relative to the total molar number of the isocyanate groups, and more preferably 10 to 55% are blocked. To achieve this blocking ratio, the blocking agent may be blended in such a manner as to achieve the desired blocking ratio, taking into account the molar number of active hydrogen of the blocking agent relative to the total molar number of the isocyanate groups.
[0027] The urethane prepolymer before blocking involved in this embodiment is a reaction product of a polyisocyanate, a polyol, and a chain extender such as a short-chain diol or a short-chain diamine as required, and the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate to the hydroxyl group of the polyol is preferably 1.2 to 2.5. When the equivalent ratio (NCO / OH) is 1.2 to 2.5, processability can be ensured, and a synthetic artificial leather with a good hand feel can be obtained. The equivalent ratio is more preferably 1.5 to 2.2.
[0028] Hereinafter, the polyisocyanate and polyol according to the present embodiment and other components will be described.
[0029] (Polyol) As the polyol, the number average molecular weight is preferably 700 to 6000, more preferably 1000 to 4000, and examples thereof include the following polyols.
[0030] (1) Polycarbonate diol Examples of the polycarbonate polyol include polytetramethylene carbonate diol, polypentamethylene carbonate diol, polyneopentyl carbonate diol, polyhexamethylene carbonate diol, poly(1,4-cyclohexanedimethylene carbonate) diol, and random / block copolymers thereof.
[0031] (2) Polyether polyols Examples of the polyether polyol include polyether polyols obtained by polymerizing or copolymerizing any one of alkylene oxides (ethylene oxide, propylene oxide, butylene oxide, etc.) and heterocyclic ethers (tetrahydrofuran, etc.), and specifically include polyethylene glycol, polypropylene glycol, polyethylene glycol-polytetramethylene glycol (block or random), polytetramethylene ether glycol, and polyhexamethylene glycol.
[0032] (3) Polyester polyol Examples of the polyester polyol include polyester polyols obtained by polycondensing at least one of aliphatic dicarboxylic acids (e.g., succinic acid, adipic acid, sebacic acid, glutaric acid, and azelaic acid) and aromatic dicarboxylic acids (e.g., isophthalic acid and terephthalic acid) with low molecular weight diols (e.g., ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexamethylene glycol, neopentyl glycol, and 1,4-bis(hydroxymethyl)cyclohexane).
[0033] Specific examples thereof include polyethylene adipate diol, polybutylene adipate diol, polyhexamethylene adipate diol, polyneopentyl adipate diol, polyethylene / butylene adipate diol, polyneopentyl / hexyl adipate diol, poly-3-methylpentane adipate diol, and polybutylene isophthalate diol.
[0034] (4) Polylactone polyol Examples of the polylactone polyol include polycaprolactone diol and poly-3-methylvalerolactone diol.
[0035] (5) Polyolefin polyol Examples of the polyolefin polyol include polybutadiene diol, polyisoprene diol, and hydrogenated products thereof.
[0036] (6) Polymethacrylate diol Examples of the polymethacrylate diol include α,ω-polymethyl methacrylate diol and α,ω-polybutyl methacrylate diol.
[0037] (7) Polysiloxane polyol As the polysiloxane polyol, dimethyl polysiloxane is preferred. Since it can provide lubricity, it is particularly useful when used as a coating agent.
[0038] These polyols may be used alone or in combination of two or more. From the viewpoint of long-term durability, it is preferred that the polyol contain a polycarbonate diol.
[0039] In addition, the number average molecular weight is a number average molecular weight converted into polystyrene, and can be usually obtained by measurement by gel permeation chromatography (GPC).
[0040] (Polyisocyanate) Examples of the polyisocyanate compound include toluene-2,4-diisocyanate, 4-methoxy-1,3-phenylene diisocyanate, 4-isopropyl-1,3-phenylene diisocyanate, 4-chloro-1,3-phenylene diisocyanate, 4-butoxy-1,3-phenylene diisocyanate, 2,4-diisocyanate diphenyl ether, 4,4'-methylenebis(phenylene isocyanate) (MDI), tetramethylphenylene diisocyanate, toluene diisocyanate, xylylene diisocyanate (XDI), 1,5-naphthalene diisocyanate, benzidine diisocyanate, o-nitrobenzidine diisocyanate, and Aromatic diisocyanates such as 4,4'-dibenzyl diisocyanate, aliphatic diisocyanates such as methylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate and 1,10-decamethylene diisocyanate, alicyclic diisocyanates such as 1,4-cyclohexylene diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,5-tetrahydronaphthalene diisocyanate, isophorone diisocyanate, hydrogenated MDI and hydrogenated XDI, or polyurethane prepolymers obtained by reacting these diisocyanate compounds with low molecular weight polyols or polyamines so as to have isocyanate terminals, etc.
[0041] (Chain Extender) (1) Short-chain diols Short-chain diols are compounds having a number average molecular weight of less than 500, and examples thereof include aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexamethylene glycol and neopentyl glycol, and low molar addition products of alkylene oxides (number average molecular weight of less than 500), alicyclic diols such as 1,4-bishydroxymethylcyclohexane and 2-methyl-1,1-cyclohexanedimethanol, and low molar addition products of alkylene oxides (number average molecular weight of less than 500), aromatic diols such as benzyl alcohol, and low molar addition products of alkylene oxides (number average molecular weight of less than 500), bisphenols such as bisphenol A, thiobisphenol and sulfonylbisphenol, and low molar addition products of alkylene oxides (number average molecular weight of less than 500), and alkyl dialkanolamines such as C1-C18 alkyl diethanolamine. In addition, diols containing ionic groups such as a carboxyl group, a sulfone group, a phosphoric acid group, and an amino group can be used.
[0042] (2) Short-chain diamines Examples of the short-chain diamine include aliphatic diamine compounds such as ethylenediamine, trimethylenediamine, hexamethylenediamine, and octamethylenediamine; aromatic diamine compounds such as phenylenediamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 4,4'-methylenebis(aniline), 4,4'-diaminodiphenyl ether, and 4,4'-diaminodiphenyl sulfone; alicyclic diamine compounds such as cyclopentanediamine, cyclohexanediamine, 4,4-diaminodicyclohexylmethane, 1,4-diaminocyclohexane, and isophoronediamine; and hydrazines such as hydrazine, carbodihydrazide, adipic acid dihydrazide, sebacic acid dihydrazide, and phthalic acid dihydrazide.
[0043] The above are examples of preferred components, and the present invention is not limited thereto. Therefore, not only the above-mentioned exemplified components but also other currently commercially available compounds that are easily available on the market can be used.
[0044] Furthermore, epoxy resin, polyvinyl chloride, or the like may be used in combination with the urethane prepolymer within a range not impairing the effects of the present invention.
[0045] (Method for preparing urethane prepolymer) The urethane prepolymer involved in this embodiment can be prepared, for example, as follows: with an equivalent ratio (NCO / OH) of isocyanate group to active hydrogen-containing group (hydroxyl group, etc.) of 1.2 to 2.5, a polyol and a polyisocyanate and a chain extender such as a short-chain diol or a short-chain diamine as required are reacted at 20 to 150° C. (preferably 60 to 110° C.) by a one-step method or a multi-step method until the product reaches a theoretical NCO% and then a prescribed amount of a blocking agent is mixed and reacted.
[0046] In the above-mentioned preparation method, a catalyst may be used as required, for example, salts of metals and organic and inorganic acids such as dibutyltin laurate, dioctyltin laurate, stannous octoate, lead octoate, tetra-n-butyl titanate, and organometallic derivatives, organic amines such as triethylamine, and diazabicycloundecene-based catalysts.
[0047] The urethane prepolymer is preferably reacted in a solvent-free state without using an organic solvent. In this way, a solvent-free urethane prepolymer can be obtained.
[0048] Additives may be added to the urethane prepolymer as needed, for example antioxidants (hindered phenol, phosphite, thioether, etc.), light stabilizers (hindered amine, etc.), ultraviolet absorbers (benzophenone, benzotriazole, etc.), gas discoloration stabilizers (hydrazine, etc.), metal deactivators, etc., or two or more thereof.
[0049] The urethane prepolymer according to the present embodiment as described above is particularly suitable for use in adhesives, laminates, coating agents, synthetic leathers, and the like.
[0050] [2. Adhesive] The adhesive of this embodiment is composed of the urethane prepolymer of the present invention. In the adhesive of this embodiment, appropriate amounts of thermoplastic polymers, tackifying resins, catalysts, pigments, antioxidants, ultraviolet absorbers, surfactants, flame retardants, fillers, foaming agents, etc. can be mixed as needed, and it is preferably composed of polyurethane prepolymer. In addition, the adhesive of this embodiment is preferably used for synthetic leather, that is, it is an adhesive for synthetic leather.
[0051] The adhesive of this embodiment can be applied to the surface of the adherend to easily bond the adherends to each other. As the adherend, in addition to the above-mentioned substrate for synthetic leather, for example, metal and non-metal (polycarbonate, glass, etc.) substrates can be cited.
[0052] [3. Laminated body] The laminate of the present invention has a moisture-cured layer of a coating film containing the adhesive of the present invention on a base film.
[0053] Examples of the substrate film include, in addition to the substrate film for synthetic leather, optical films and optical plates, flexible printed circuit boards, glass substrates, and substrates obtained by vapor-depositing ITO on these substrates.
[0054] The laminate of the present invention can be obtained by coating the adhesive of the present invention on a substrate film by a known method such as comma coating, knife coating, roll coating, and moisture curing the adhesive to form a moisture cured layer from the coating film.
[0055] [4.Synthetic leather] The synthetic artificial leather of the present invention has a thermally pressed product of a base fabric on the moisture-cured product layer of the laminate of the present invention.
[0056] Examples of base fabrics include fabrics made of twill fabrics, plain fabrics, etc., pile fabrics obtained by mechanically raising the cotton raw material of the fabric, rayon fabrics, nylon fabrics, polyester fabrics, Kevlar fabrics, non-woven fabrics (polyester, nylon, various latexes), various films, sheets, etc.
[0057] The synthetic artificial leather can be produced, for example, as follows: A base fabric is laminated on the moisture-cured layer of the laminate of the present invention and pressed at 75 to 155° C. Further, aging is performed as necessary to obtain the synthetic artificial leather of the present invention.
[0058] The synthetic artificial leather as described above is suitable for shoes, clothes, bags, furniture, vehicle interior materials (eg, dashboards, doors, consoles, seats), and the like. Example
[0059] Next, the present invention will be described in further detail by way of Examples and Comparative Examples, but the present invention is not limited to Examples, etc. The number average molecular weight is measured by GPC (polystyrene conversion).
[0060] [Example 1] 100 parts by mass of a polyester polyol with a number average molecular weight of 2000 composed of adipic acid and 1,4-butanediol and 25 parts by mass of 4,4'-diphenylmethane diisocyanate (MDI) were placed in a 500 ml glass reaction container equipped with a stirrer, a thermometer, a gas inlet, etc., heated and decompressed to dehydrate, and then sealed with nitrogen to make the internal temperature 100°C, and stirred for 120 minutes. It should be noted that NCO / OH=2.0. Then, 2.4 parts by mass of 1-hexadecanol were reacted as a blocking agent to obtain a urethane prepolymer.
[0061] [Examples 2 to 5 and Comparative Examples 1 and 2] Except having used the formulation shown in Table 1, the same procedure as in Example 1 was carried out to obtain a urethane prepolymer.
[0062] The viscosity, thermal softening temperature and adhesive strength of the urethane prepolymer prepared in each example were measured as follows.
[0063] (Viscosity measurement) The viscosity of each urethane prepolymer was measured using a BM type viscometer (Tokyo Keiki Co., Ltd.) under the conditions of No. 4 rotor / 30 rpm / 100°C.
[0064] (Thermal softening temperature measurement) (1) Sample preparation The urethane prepolymer heated to 100°C was coated on release paper to a film thickness of 50 μm, aged at 25°C / 60 RH% for more than 48 hours, and then peeled off from the release paper to obtain a translucent film with a width of 1.5 cm and a length of 6 cm. Figure 1 As shown, clips 12 are installed above and below the translucent film 10, and the clips 12 are further fixed with Cellotape (registered trademark). A weight 14 is installed so that when the sample is suspended on one of the clips 12, a force of 450 g / cm is applied. 2 A load of 100 was applied to prepare a sample 16. It should be noted that the central portion of the film 10, 2 cm in the longitudinal direction, was not covered with Cellotape (registered trademark).
[0065] (2) Determination like Figure 2As shown, the clip 12 without the weight 14 of the sample 16 of each example was mounted on the turntable 22 of the Gill heat aging box 20. Then, the temperature in the Gill heat aging box 20 was raised from room temperature at a rate of 3°C / min while the turntable 22 was rotated at 5 rpm. The temperature at which the film 10 broke or stretched to 2 times was taken as the softening point.
[0066] (Adhesion Strength) (1) Membrane preparation The urethane prepolymer heated to 100° C. was coated on release paper to a film thickness of 50 μm, aged at 25° C. / 60 RH% for 48 hours or more, and then peeled from the release paper to obtain a translucent film.
[0067] (2) Lamination The film obtained above was sandwiched from the top and bottom using a test polyester mesh base cloth, and was heat-pressed at 150° C. for 5 seconds from the top to prepare a 20 mm wide strip-shaped measurement sample.
[0068] (3) Determination The adhesive strength was measured by pulling at a speed of 200 mm / min using Autograph AGS-J (Shimadzu Corporation). Since it was 0.3 kgf / cm or more, it was judged that the adhesiveness exceeded the level that would not cause any practical problems when using the above substrate.
[0069] [Table 1] (Manufacturing of synthetic leather) RESAMINE NE-8875-30M (Dainichi Seika Industries, Ltd.) was applied onto release paper to a film thickness of 40 μm, and dried at 120° C. / 5 minutes to obtain a skin layer.
[0070] On the other hand, the moisture-curable adhesive described in Example 1 was applied onto release paper so as to have a film thickness of 100 μm, and aged under the conditions of 25° C. / 60 RH% for 48 hours to obtain an adhesive layer.
[0071] The obtained adhesive layer was peeled off from the release paper, and sandwiched between the surface layer and the base cloth of the test polyester mesh raw material. The release paper side of the surface layer was laminated using a heat source sealer at 170°C / 0.15MPa / 30 seconds. Finally, the release paper of the surface layer was peeled off to produce a synthetic leather. The obtained synthetic leather had a good feel.
[0072] Explanation of symbols 10 Film 12 Clips 14 weights 16 samples 20 Gill Heat Aging Chamber 22 turntable
Claims
1. Urethane prepolymers having isocyanate groups, The viscosity at 100°C is 30 to 600 dPa·s, and The thermal softening temperature after moisture curing is 75~155℃. The urethane prepolymer is a reactant of polyisocyanate and polyol, and the polyisocyanate is 4,4'-diphenylmethane diisocyanate, Among the isocyanate groups, 10 to 55% of the isocyanate groups relative to the total molar number are blocked by at least one blocking agent selected from aliphatic alcohols having 10 or more carbon atoms, aliphatic amines, alicyclic amines, aromatic amines, imidazoles and pyrazoles, The above-mentioned heat softening temperature is the temperature at which the film breaks or stretches to 2 times after the clip of the sample without a weight is mounted on the turntable of the Gill heat aging box, while the turntable is rotated at 5 rpm and the temperature in the Gill heat aging box is raised from room temperature at a rate of 3°C / min. The above-mentioned sample is prepared as follows: a urethane prepolymer heated to 100°C is coated on a release paper so that the film thickness is 50 μm, and the film is aged at 25°C / 60RH% for more than 48 hours, and then peeled from the release paper to obtain a translucent film with a width of 1.5 cm and a length of 6 cm. Clips are mounted above and below the translucent film, and the clips are further fixed. When the film is mounted on a clip and hung, a pressure of 450 g / cm is applied. 2 The load of such weights. 2 . The urethane prepolymer according to claim 1 , which is a reaction product of a polyisocyanate and a polyol, and an equivalent ratio (NCO / OH) of an isocyanate group of the polyisocyanate to a hydroxyl group of the polyol is 1.2 to 2.
5.
3. The urethane prepolymer according to claim 1, wherein The blocking agent is at least one selected from aliphatic alcohols having 10 or more carbon atoms, aliphatic amines, alicyclic amines and aromatic amines. 4 . An adhesive comprising the urethane prepolymer according to claim 1 .
5. A laminate, wherein: A moisture-cured layer of a coating film containing the adhesive according to claim 4 is provided on a base film.
6. Synthetic leather, of which: The laminate according to claim 5 has a thermal compression product of a base fabric on the moisture-cured product layer.
Citation Information
Patent Citations
Polyurethane resin and its production
JP2000336142A
Polyurethane resin composition and hot melt adhesive using the same
JP2005126595A